2017
DOI: 10.1111/acfi.12304
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the CEO's value perception towards auditing on audit demand in private firms

Abstract: Audit demand is generally considered to be a direct reflection of the level of agency conflicts. This study examines the CEO's value perception towards auditing as additional driver for both auditor reputation demand (appointing a Big 4 auditor or not) and audit effort demand in private firms. Examining the CEO's value perception in a multidimensional way, the regression results indicate that the CEO's functional value perception towards auditing positively affects the demand for audit effort, while the CEO's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 88 publications
(252 reference statements)
1
7
0
Order By: Relevance
“…Most empirical studies also support this hypothesis based on agency theory as they find a positive association between agency conflicts and auditor choice (e.g., [2][3][4]14]). As the sample firms in most of these studies already had a statutory audit requirement, auditor choice was generally operationalized as the choice for a Big Four auditor versus a non-Big Four auditor.…”
Section: Auditor Choice and Agency Conflictsmentioning
confidence: 97%
See 4 more Smart Citations
“…Most empirical studies also support this hypothesis based on agency theory as they find a positive association between agency conflicts and auditor choice (e.g., [2][3][4]14]). As the sample firms in most of these studies already had a statutory audit requirement, auditor choice was generally operationalized as the choice for a Big Four auditor versus a non-Big Four auditor.…”
Section: Auditor Choice and Agency Conflictsmentioning
confidence: 97%
“…Additionally, in the context of firms having a statutory audit requirement, willingness seems to play an important role as well. In that setting, Corten, Steijvers, and Lybaert [14] found that positive managerial perceptions towards auditing lead to a higher probability of appointing a Big Four auditor. Thus, it seems that if management perceives an audit to be useful, it is more willing to appoint a Big Four auditor.…”
Section: Willingness Of Management To Influence Auditor Choicementioning
confidence: 98%
See 3 more Smart Citations